The Relationships Amongst Pediatric Nurses' Work Environments, Work Attitudes, and Experiences of Burnout - Buckley, Laura; Berta, Whitney; Cleverley, Kristin; Widger, Kimberley (Frontiers in Pediatrics, 2021)
Paediatric nurses care for some of the most vulnerable patients in our healthcare system. Research at the intersection of nursing science and organizational behaviour shows that the quality of care nurses provide is directly related to their well-being, influenced by Burnout and job stress, in the workplace. However, much of the research conducted on nursing populations neglects to separately study nurses who care for children. In a resource limited system where health care provider well-being is recognized as a priority, it is important for administrators to understand the environmental and attitudinal work factors most influential to paediatric nurse work outcomes in order to target optimization strategies. The aim of the study was to identify which modifiable work environment factors make the greatest contribution to the work outcome of Burnout in paediatric nurses. A cross-sectional survey design was used at a large quaternary care paediatric hospital in Toronto, Canada. We administered a survey to a convenience sample of all registered nurses with >3months experience in the Paediatric, Cardiac, and Neonatal Intensive Care Units from January 2021 – March 2021. Path analysis was used to test our proposed model which was specified a priori based on a review of the literature. 143 nurses completed the survey. Path analysis of the tested model resulted in good fit. Quality of Work-life had the largest direct effect on Work Engagement (=0.62, S.E.=0.09). Work Engagement had the largest direct effect on Personal Accomplishment (=.68, S.E.=.53). Quality of Work-life had the largest indirect effect on Personal Accomplishment (=.4, S.E.=.65), Emotional Exhaustion (=-.33, S.E.=.87), and Depersonalization (= -.17, S.E.=.41), respectively. Work Engagement had the largest total effect on Personal Accomplishment (=.68, S.E.=.64) and the third largest total effect on Emotional Exhaustion (=-.57, S.E.=.83). Quality of Work-life had the second largest total effect on Work Engagement (=.58, S.E.=.11) indicating that Quality of Work-life is mediated through Work Engagement for its effect on Burnout. Our results indicate work environment and work attitude factors that can provide organizational leadership with a targeted focus to reduce paediatric critical care nurse Burnout, and thus improve provider well-being, in a resource limited system.